Strategy for Developing a High-End Local Brand Business to Increase Consumer Loyalty among Active Business Administration Students at UPN Veteran East Java Who Use The Buttonscarves Fashion Brand - RA Tania Eriezna Putri; Acep Samsudin (International Journal of Social, Economic, and Business, 2025)
Halal fashion is one of the important segments in the halal industry that supports Indonesia's economy. Amidst the fierce competition in the Indonesian fashion market, Buttonscarves has successfully achieved the status of a luxury brand in Indonesia, attracting global attention with the uniqueness and luxury of its products. The focus of this research is on how marketing strategies and customer experiences can create a deep relationship between the brand and its consumers, thereby fostering sustainable loyalty. This research uses qualitative methods. In this research, the focus is on the theoretical perspective of consumer behavior studies, which emphasizes how individuals make decisions based on their needs, preferences, and experiences. The objects of study in this research are the Buttonscarves offline store branch in Surabaya and Business Administration students at UPN Veteran East Java. The data analysis in this study uses SWOT analysis. The results of this study, based on the SWOT matrix analysis in the diagram above, can be concluded that Buttonscarves is in Quadrant I with coordinates (X;Y),which reflects the implementation of an aggressive strategy. Based on the Internal-External Matrix analysis, Buttonscarves is located in quadrant IV with coordinates (x;y) of (3.18; 3.42). This position indicates that the company is in the Grow and Build stage.